Analysis of the 'Dutch Disease' Effect on the Selected Resource‐Rich ASEAN Economies. Issue 2 (16th April 2018) - Taguchi, Hiroyuki; Khinsamone, Soukvisan
Abstract: This article examines the applicability of the Dutch Disease hypothesis by using a vector auto‐regression model, focusing on the resource‐rich and middle‐income economies in the Association of Southeast Asian Nations. The empirical study found that the latecomers of Lao People's Democratic Republic and Myanmar seemed to suffer from the Dutch Disease over the sample period for 1970–2015; and the forerunners of Indonesia and Malaysia, on the other hand, appeared to have no Dutch Disease effect at least in the current period of 1997–2015, although Indonesia had experienced the Dutch Disease in the previous period of 1970–1996. The lessons from the forerunners' experiences in order for the latecomers to escape from the Dutch Disease are to establish some funding system of allocating resource revenues for investment projects; to diversify domestic industries through improving business environments; and to improve institutional quality to reinforce resource governance.